PENGARUH NON PERFORMING LOAN (NPL), NET INTEREST MARGIN (NIM) DAN LOAN TO DEPOSIT RATIO (LDR) TERHADAP PERUBAHAN LABA PADA BANK DEVISA DAN BANK NON DEVISA DI INDONESIA TAHUN 2006-2010 - MINAR SAVITRI, DHIAN ANDANARINI (STIE Totalwin Semarang, 2011)
The performance of the companys management expects higher earnings changes and flexibility ofÂ companyâs operation activities. Â Estimates of future earnings changes can be made by analyzing financial statements. In banking, an increase in profits can be used by management to improve or strengthen its capital structure to withstand such profits. So the opportunity Â was the chance of funding that require substantial funds can be readily handled by the bank. Samples of this study was taken in the 42 banks that Divided into 26 foreign exchange banks and 16 non bank foreign exchangeÂ with purposive sampling methods. The data analyzed by multiple regression tests which previously performed test of normality, the assumption of classical test irregularities (multicollinearity, autocorrelation and heteroscedasticity), hypothesis testing (t and F) and test of coefficient determinations. The results obtained non-performing loans (NPLs) and loan to deposit ratio (LDR) was not shown significant negative effects and changes Â on foreign exchange earnings in the banking system and the Non-Foreign Exchange. Net interest margin (NIM) was not shown significant positive effects on earnings of changes in Foreign Exchange and Non-bank Foreign Exchange.